cAMP signalling of Bordetella adenylate cyclase toxin through the SHP-1 phosphatase activates the BimEL-Bax pro-apoptotic cascade in phagocytes - Ahmad, Jawid Nazir; Cerny, Ondrej; Linhartova, Irena; Masin, Jiri; Osicka, Radim; Sebo, Peter (Cellular microbiology, 2016)
The adenylate cyclase toxin-hemolysin (CyaA, ACT or AC-Hly) plays a key role in virulence of Bordetella pertussis. CyaA penetrates myeloid cells expressing the complement receptor 3 (αM β2 integrin CD11b/CD18) and subverts bactericidal capacities of neutrophils and macrophages by catalysing unregulated conversion of cytosolic ATP to the key signalling molecule adenosine 3',5'-cyclic monophosphate (cAMP). We show that the signalling of CyaA-produced cAMP hijacks, by an as yet unknown mechanism, the activity of the tyrosine phosphatase SHP-1 and activates the pro-apoptotic BimEL-Bax cascade. Mitochondrial hyperpolarization occurred in human THP-1 macrophages within 10 min of exposure to low CyaA concentrations (e.g. 20 ng ml(-1) ) and was accompanied by accumulation of BimEL and association of the pro-apoptotic factor Bax with mitochondria. BimEL accumulation required cAMP/protein kinase A signalling, depended on SHP-1 activity and was selectively inhibited upon small interfering RNA knockdown of SHP-1 but not of the SHP-2 phosphatase. Moreover, signalling of CyaA-produced cAMP inhibited the AKT/protein kinase B pro-survival cascade, enhancing activity of the FoxO3a transcription factor and inducing Bim transcription. Synergy of FoxO3a activation with SHP-1 hijacking thus enables the toxin to rapidly trigger a persistent accumulation of BimEL, thereby activating the pro-apoptotic programme of macrophages and subverting the innate immunity of the host.
Keywords: Mitochondria; Adenylate Cyclase Toxin; Forkhead Transcription Factors; signální transdukce; fagocyty; Membrane Proteins; Signal Transduction; tyrosinfosfatasa nereceptorového typu 6; bordetella; AMP cyklický; Forkhead Box Protein O3; Humans; protein BCL2L11; Host-Pathogen Interactions; interakce hostitele a patogenu; forkhead transkripční faktory; makrofágy; lidé; mitochondrie; Bordetella pertussis; virulence; Cyclic AMP; protoonkogenní proteiny; apoptóza; Phagocytes; Apoptosis Regulatory Proteins; cell injury/sublethal injury; toxins; Proto-Oncogene Proteins; protein FOXO3; proteiny regulující apoptózu; membránové proteiny; bcl-2-Associated X Protein; protein X asociovaný s bcl-2; Macrophages; adenylátcyklasový toxin; Protein Tyrosine Phosphatase, Non-Receptor Type 6; microbial-cell interaction; Apoptosis; Bcl-2-Like Protein 11